The olfactory mucosa: a potential source of stem cells for hearing regeneration. (16th August 2018) - Young, Emily; Westerberg, Brian; Yanai, Anat; Gregory-Evans, Kevin
The olfactory mucosa contains cells that enable it to generate new neurons and other supporting cells throughout life, allowing it to replace cells of the mucosa that have been damaged by exposure to various insults. In this article, we discuss the different types of stem cell found within the olfactory mucosa and their properties. In particular, the mesenchymal-like cells found within the lamina propria will be reviewed in detail. In addition, we discuss potential applications of olfactory-derived stem cells toward hearing regeneration secondary to either inner hair cell loss or primary or secondary auditory nerve degeneration.